Literacy about Covid-19: Trending Words, News Sources, Comprehension, and Community Curiosity in Perspectives Nonformal Education - Hardika, Hardika; Aisyah, Eny Nur; Kurniawan, Taufik (Journal of Nonformal Education, 2020)
Covid-19 pandemic has presented a lot of learning for the community through various new information and vocabulary related to the nature and meaning of Covid-19. The emergence of this new vocabulary is responded to and understood differently in the community. This study aims to identify and explain the phenomenon of the emergence of trending words (trend words) about Covid-19, news sources, understanding, and curiosity (curiosity) of the public about trending words Covid-19 in the perspective of non-formal education. The study was conducted with a quantitative descriptive approach by taking the population of Malang Raya, which included Malang City, Malang Regency, and Batu City. The sample was chosen purposively by considering the research process must be carried out quickly, data collection should not be done physically close together, and respondents must have an android mobile phone to fill in the instruments in Google Form. Data was collected using a closed questionnaire technique that was distributed through the Google Form Information Technology Application. Data analysis was performed using percentage descriptive statistics. The results showed that (1) there was the addition of new vocabulary about Covid-19, and (2) there were variations in sources, understanding, and curiosity about news and the meaning of vocabulary about Covid-19.